Posted - Anderson, John David 1975- (New York, NY Walden Pond Press, an imprint of HarperCollins Publishers, 2017)
In middle school, words aren't just words. They can be weapons. They can be gifts. The right words can win you friends or make you enemies. They can come back to haunt you. Sometimes they can change things forever. When cell phones are banned at Branton Middle School, Frost and his friends Deedee, Wolf, and Bench come up with a new way to communicate: leaving sticky notes for each other all around the school. It catches on, and soon all the kids in school are leaving notes -- though for every kind and friendly one, there is a cutting and cruel one as well. In the middle of this, a new girl named Rose arrives at school and sits at Frost's lunch table. Rose is not like anyone else at Branton Middle School, and it's clear that the close circle of friends Frost has made for himself won't easily hold another. As the sticky-note war escalates, and the pressure to choose sides mounts, Frost soon realizes that after this year, nothing will ever be the same
Ages 8-12
1
Keywords: Bullies -- Fiction; Bullying in schools -- Juvenile fiction; Bullying in schools; Education -- Fiction; Fiction for children; Friendship -- Fiction; JUVENILE FICTION / School & Education; JUVENILE FICTION / Social Themes / Bullying; JUVENILE FICTION / Social Themes / Friendship; Juvenile fiction; Middle school students -- Juvenile fiction; Middle school students; Sticky notes -- Juvenile fiction; Sticky notes; Written communication -- Juvenile fiction; Written communication; New students -- Fiction; Schools -- Fiction; Sticky notes -- Fiction; Written communication -- Fiction; Bullying -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Fiction; Juvenile works